Repeating late-phase pseudo-progression in a patient with non-small cell lung cancer treated with long-term nivolumab monotherapy; a case report - Ebisuda, Rikako; Furuya, Naoki; Inoue, Takeo; Kaneko, Shotaro; Numata, Yu; Shinozaki, Yusuke; Mineshita, Masamichi (Frontiers in Oncology, 2024)
Background: Immune check point inhibitors (ICIs) are standard treatment for patients with non-small cell lung cancer (NSCLC). Nearly a decade has passed since nivolumab was approved by the FDA for NSCLC patients. However, long-term outcomes and clinical features remain unclear for individual cases. Pseudo-progression is a well-known paradoxical radiological response pattern under ICI treatment which occurs when tumor index lesions regress after apparent initial progression. We herein report a unique case of NSCLC with repeating pseudo-progression in late phase treated with nivolumab monotherapy for 8.5 years.Case Presentation: A 56-year-old male diagnosed with Non-sq NSCLC clinical stage IVA, at the left upper lobe primary lesion. The primary lesion was PD-L1 negative with no oncogenic driver mutations. He had multiple pulmonary metastases and a left adrenal gland metastasis, and subsequently, received nivolumab as third-line therapy. After initiation of nivolumab, the lung lesion and adrenal metastasis shrank rapidly; however, the patient experienced three late-phase pseudoprogressions in the mediastinal lymph node (LN). This patient is still receiving nivolumab with no symptoms and PS 0. Acquired resistance should be judged carefully in patients with LN-only oligoprogression to avoid unnecessary local therapies and the misjudgment of treatment.